The Art of Time Travel: Historians and their Craft. (March 2017) - Day, David
Abstract : The Art of Time Travel: Historians and their Craft. By Tom Griffiths (Melbourne: Black Inc., 2016), pp. xviii + 326. AU$34.99 (pb).